Effect of acidity regulators on the shelf life, quality, and physicochemical characteristics of fresh wet noodles. (January 2022) - Han, Tian-Yang; Yang, Zhen; Yu, Chen; Xing, Jun-Jie; Guo, Xiao-Na; Zhu, Ke-Xue
Abstract: In this study, the effects of acidity regulators (ARs) on the shelf life, quality, and physicochemical characteristics of fresh wet noodles (FWNs) were investigated. The addition of ARs markedly reduced the pH value of FWNs with a prolonged microbial shelf life of 5–10 days. Moreover, the presence of ARs significantly ( p  < 0.05) decreased the hardness and tensile distance of cooked FWNs, while increasing the cooking loss of noodles significantly ( p  < 0.05). The results of confocal laser scanning microscope analysis showed that ARs inhibited the formation of gluten networks in cooked noodles. Sodium dodecyl sulfate-extractable protein (SDS-EP) and free –SH content increased significantly ( p  < 0.05) when ARs were added. ARs affected the polymerization of proteins by inhibiting the formation of interchain disulfide bonds during cooking. Moreover, X-ray diffraction results showed that the addition of ARs resulted in acid hydrolysis of the amorphous area of the starch in FWNs, decreasing the pasting temperature, peak and trough viscosities of the starch. The reduction in pH value was the main factor that affected the shelf life and quality of FWNs, but different types of ARs had no significant impact. Graphical abstract: Image 1 Highlights: Adding acidity regulators (ARs) markedly prolonged shelf life of fresh wet noodles. ARs reduced the hardness and elasticity of noodles and increased cooking loss. ARs inhibited the formation of protein networks during cooking. A decrease in pH value inhibited the formation of interchain disulfide bonds. ARs changed the pasting properties and relative crystallinity of starch in noodles.